The Comparison Between Microwave and Autoclave as Antigen Retrieval Methods for Immunohistochemical Detection of CD15 and CD30 in Hodgkin’s Lymphoma - Kosari, Farid (Iran J Pathol, 2018)
BACKGROUND AND OBJECTIVE: Hodgkin's lymphoma is a potentially curable hematologic malignancy with difficulty in its diagnosis especially in atypical cases even in expert hands. Today, immunohistochemistry plays a significant role in the diagnosis of it especially applying the anti-CD15 and anti-CD30 antibodies. The negativity of CD15 can be reduced by antigen retrieval for methods. In this study, the effect of autoclave was compared with microwave as heating sources of antigen retrieval in immunohistochemical staining. METHODS: Sections prepared from 50 formalin-fixed paraffin-embedded tissue blocks of Classic Hodgkin's lymphomas stained for CD15 and CD30 using autoclave and microwave, were randomly and blindly reviewed by an expert hematopathologist, mostly focusing on Reed-Sternberg cells; the intensities were scored from 0 to +4 and analyzed by SPSS software. RESULTS: Fifty eight percent of patients were male. The mean age was 32 years (range: 7 to 77). Nodular sclerosis was the most prevalent subtype. CD15 positivity in microwave treatment was 92% compared to 50% in autoclave. Negative CD30 decreased from 20% in autoclave to 2% in microwave. Intensity of staining in both markers was at least +1 greater in microwave treatment. No background staining was seen in microwave method. CONCLUSION: There was bimodal age distribution in Hodgkin's lymphoma patients with the predominant male and Nodular Sclerosis as the most common type. Comparing autoclave and microwave, higher rate of the positivity was detected using microwave treatment, especially in CD15 staining. Improvement in staining intensity was also noticeable in both markers. There was no background or non-specific staining in microwave method. No disturbance of cells or nuclear morphology was also reported.